Peningkatan Kemampuan Membaca Pemahaman dengan Menggunakan Strategi PORPE pada Siswa Kelas IV SD - Putri, Novi Eka; Taufina, Taufina; Fitria, Yanti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The objective of this study is to describe the improvement of reading comprehension ability by using the PORPE strategy on the 4th grade students of Elementary School No.05 Bandar Buat, Padang. Research subjects were teachers and 28 students in the 4th grade of Elementary School No. 05 Bandar Buat, Padang. This study is a classroom action research that uses qualitative and quantitative approaches. The results showed that the students’ ability in reading comprehension increased from 75,1 (Enough) with 55,5% level of mastery in cycle I, to 92,7 (Very Good) with 92,9% level of mastery in cycle II. The percentage of improvement from cycle I to cycle II is 17,6 %. Based on these results, it is concluded that the PORPE strategy can improve the ability of reading comprehension of the 4th grade students of Elementary School. Keywords: Reading comprehension ability; PORPE strategy